2019
DOI: 10.3329/jbcbm.v5i1.42184
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and medicinal uses of globe artichoke (Cynara scolymus L.) plant

Abstract: Globe artichoke (Cynara scolymus L.) is a vegetable crop native of the Mediterranean basin and it is grown mainly for its immature flower buds. The edible parts of artichoke have important nutrition values to their content of inulin, fibers and minerals. Furthermore, artichoke is recognized as a medicinal plant where leaves and heads are rich source of polyphenolic compounds. It is recommended for the treatment of gallstones, liver disease or damage and poor liver function. The pharmaceutical properties of art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
2
0
1
Order By: Relevance
“…Artichoke, also known as Cynara scolymus , is another food with medicinal value [ 141 ]. Artichoke is composed of carbohydrates (6.8%) and nitrogen compounds (2.9%), with a high fiber content and low caloric value [ 142 ].…”
Section: Types Of Prebioticsmentioning
confidence: 99%
“…Artichoke, also known as Cynara scolymus , is another food with medicinal value [ 141 ]. Artichoke is composed of carbohydrates (6.8%) and nitrogen compounds (2.9%), with a high fiber content and low caloric value [ 142 ].…”
Section: Types Of Prebioticsmentioning
confidence: 99%
“…Studies conducted in different disease groups have reported that a diet rich in vegetables and fruits has a significant protective potential effect against the risk of illnesses such as hypertension, diabetes, cardiovascular diseases and cancer [1]. Artichoke (Cynara Scolymus), a vegetable known and consumed for centuries, has been accepted as a potential phytotherapeutic agent for various conditions such as cardiovascular, hepatic, liver and gastric diseases [2], [3]. It is known that artichoke leaf extract contains saponins, caffeic acid derivatives, flavonoid derivatives, fatty acids and various polyphenolic components [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…The cultivation of globe artichokes is a dynamic process that has seen a number of innovative developments in the current period. First, there is a focus on varietal improvement through Globe artichoke breeding programs, with the goal of developing artichoke varieties that exhibit improved traits such as higher yields, resistance to diseases, and enhanced flavor (Bekheet and Sota, 2019;López-Anido and Martin, 2021;Spanò et al, 2023). Additionally, optimizing cultivation practices, including planting density, irrigation methods, and pest management, plays a pivotal role in maximizing artichoke yields while conserving resources (Leskovar et al, 2013;Anwar et al, 2017;Fracchiolla et al, 2022).…”
Section: Introductionmentioning
confidence: 99%